Integrating Artificial Intelligence into Clinical Practice Guidelines: Opportunities and Challenges - Robert Anner; Yunne Agrly (Journal of Midwifery History and Philosophy, 2025)
Background: The integration of Artificial Intelligence (AI) into clinical practice guidelines has the potential to revolutionize healthcare by enhancing decision-making processes and improving patient outcomes. Despite its promising benefits, several challenges must be addressed to effectively incorporate AI into clinical guidelines. Objective: This research aims to explore the opportunities and challenges associated with integrating AI into clinical practice guidelines. The study seeks to identify the benefits AI can offer in clinical settings and the obstacles that may hinder its successful implementation. Methodology: A comprehensive review of existing literature on AI applications in healthcare was conducted, supplemented by expert interviews and case studies of AI implementations in clinical practice. The research analyzed AI’s impact on clinical decision-making, guideline development, and patient outcomes. Results: The findings reveal that AI integration can significantly enhance clinical practice guidelines by providing data-driven insights, improving accuracy, and personalizing patient care. However, challenges such as data privacy concerns, algorithmic bias, and the need for robust validation processes were also identified as significant barriers. Conclusion: Integrating AI into clinical practice guidelines offers substantial opportunities for improving healthcare delivery but requires careful consideration of associated challenges. Addressing these challenges through rigorous validation, ethical guidelines, and ongoing education will be essential for maximizing AI’s benefits in clinical settings. Future research should focus on developing strategies to overcome these barriers and ensure effective AI integration.